MODIFIKASI NANOPARTIKEL PERAK DENGAN ASAM p-HIDROKSIBENZOAT DAN GLISIN UNTUK DETEKSI KOLORIMETRI ION Ni²⁺ - Sari, Gladis Raspida; Gusrizal, Gusrizal; Ardiningsih, Puji (Tanjungpura University, 2025)
Silver nanoparticles (AgNPs) are well known for their unique physicochemical properties and have been widely applied in sensing technologies, particularly as colorimetric sensors for metal ions. In this study, AgNPs were synthesized using p-hydroxybenzoic acid, which functioned as both a reducing and capping agent to ensure controlled particle growth and stability. The aim was to develop a simple and sensitive method for detecting Ni²⁺ ions using these AgNPs, with glycine added as a ligand to enhance the sensing performance. The detection was based on observable color changes and absorbance shifts in the UV-Vis spectrum resulting from interaction between AgNPs and Ni²⁺ ions. The results showed that the presence of glycine significantly enhanced the AgNPs’ response to Ni²⁺, indicating a synergistic effect that improved detection sensitivity. The method demonstrated good linearity, with a coefficient of determination (R²) of 0.993. The calculated limit of detection (LOD) was 3.0 × 10⁻⁴ M, and the limit of quantification (LOQ) was 9.9 × 10⁻⁴ M. Precision analysis showed that the percent relative standard deviation (%RSD) was within acceptable limits, remaining below two-thirds of the coefficient of variation (%CV) defined by the Horwitz equation. These findings confirm that the modified AgNP-based system is both reliable and effective for the colorimetric detection of Ni²⁺ ions in solution.